Analisis Kestabilan Lereng Lowwall Section A dan Section B Pit Middle Menggunakan Limit Equilibrium Method (Morgenstern-Price) di Tambang Terbuka PT. Banjarsari Pribumi, Kecamatan Merapi Timur, Kabupaten Lahat, Sumatera Selatan - M Iqbal Alfidqi Fauzi; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2022)
This study focuses on the Lowwall Pit Middle Slope which is divided into 2 Sections, namely Slope Section A and Slope Section B. In the crest section of the slope there is a disposal area. From the results of field observations, water seepage was found at RL ± 40 mdpl and RL ± 70 mdpl. In addition, cracks were found at RL±90 mdpll and RL±100 mdpl in the disposal area. The impact of this finding is the landslide that occurred on the Lowwall Section A Slope. In addition, the high rainfall at PT. Banjarsari Pribumi causes the value of cohesion and shear angle in the material making up the slopes to decrease. The method used in analyzing the stability of the Lowwall Pit Middle Slope is the Limit Equilibrium (Morgenstern-Price) method which is applied in slide 6.0 software. The analysis was carried out based on the topography of December 2021. The results of the stability analysis of the Lowwall Pit Middle Slope for Section A obtained that the saturated FK was 1.072 and the saturated FK Section B was 1.192. From the analysis results obtained, it is explained that the Lowwall Pit Middle Slope is in a critical condition. For this reason, the authors carry out simulations of actual slope dewatering and simulation of resloping + dewatering of the Lowwall Pit Middle Slope. The results of the 5 m dewatering simulation for section A obtained the FK value of 1,352 and for section B of 1,306. The results of the resloping + dewatering simulation for section A obtained the FK value of 1.542 and for section B of 1.384.